ALTERNATIVE MECHANISM ON REDD INCENTIVE DISTRIBUTION THROUGH FUND BALANCING BETWEEN CENTRAL TO REGIONAL GOVERNMENT - Indartik Indartik; Fitri Nurfatriani; Kirsfianti Linda Ginoga (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2010)
Incentive from REDD mechanism is needed for developing countries in creating compensation to prevent forest from conversion to other uses. Incentive distribution mechanism regulates the proportional distribution of incentives and responsibilities between the parties which are the central government, local governments, communities, investors and other parties concerned. This mechanism is required in the implementation of REDDin the future. This paper aims to design a mechanism for distribution of REDDincentives through the rules of central-local budgets distribution that already exist. The research method used in this study was content analysis to see the possibility of designingREDDincentive distribution mechanism based on existing policy and the expectations of the parties involved in this activity. The research was conducted in Central Kalimantan and South Sumatera in 2009. The results showed that in the proposed REDD incentivedistribution mechanisms, payments from the voluntary market can be received directly by the manager, whereas in the compliance market should be through the central government. The proportion of benefits distribution for central and local government is proposed to follow the rules in distribution of Revenue Sharing Funds from the Reforestation Fund inaccordance with government regulations (PP) 55 / 2005 concerning the balance funds 60% for central government and 40% for local governments. This proportion is based on the implementation of REDD national approach with a broad range of technical and institutional cross-sectoral activities. The success of REDD implementation depend on the commitment of land owners to maintain the level of emission reductions from the previous land use practices. Thus, enforcement agreement with land owners is needed.